Gradual distraction on hinged-based Ilizarov ring fixator to correct fixed flexion deformity of knee: description of the surgical technique - Regmi, Anil; Niraula, Bishwa B.; Bansal, Shivam; Gowda, Rohan; Barman, Saptarshi; Dhingra, Mohit (International Journal of Research in Orthopaedics, 2023)
Knee deformity in flexion is the most disabling deformity. Surgical correction can be attempted with soft tissue release, osteotomy, or both. However, acute correction can cause serious complications. Ilizarov technique has become an appealing alternative to open surgery, where skeletal traction is used to distract the joint gradually and steadily in order to reduce the risk of skin problems or neurovascular injuries. Two patients and three limbs, male aged 28-42 (mean=35 years) with severe fixed flexion deformity were corrected by a hinged-based Ilizarov ring fixator. Mean flexion of the knee was pre-operatively 86.66 degrees (80-90 degrees). The mean extension angle at the last follow-up was 168.3 degrees (165-170). The mean knee society score (KSS) was 44.3 (35-50), mean KSS functional score was 43.3 (0-65). One patient had satisfactory outcomes and could stand without walking aids and walks on extended knee with walking aids. Arthrodesis of knee or creating a stiff knee in the most extended position may be most effective for severe, fixed contractures.With the gradual, calculated distraction, the Ilizarov apparatus is an effective tool for treating severe cases of knee contracture.